Investigation of the photonic time stretch for frequency agility in communication systems - Selerio, Fatima B.; Marciano, Joel Joseph S. Jr.; Hilario, Paul Leonard Atchong (Quezon City College of Engineering, University of the Philippines Diliman, 2019)
Frequency agility in systems is a characteristic that is recently explored to address spectrum scarcity. Spectrum scarcity is growing concern, especially at the higher end of the frequency spectrum, which mobile systems use. A possible technique that can aid spectrum scarcity is to lower the frequency of our signals, to lower their bandwidth requirement. A type of frequency conversion, that is gaining much interest,is photonic time stretching (PTS). PTS utilizes chromatic dispersion in optical fibers to reduce the frequency of RF signals. Most of its current applications focus on reducing bandwidth for analog-to-digital converters. It show great promise for communication systems, but it needs a characterization of its effects. For this study, we investigated the effects of the PTS system, particularly on its power efficiency, frequency components, and practical implementation. We developed a simulation test bed using MATLAB. Our test bed was able to stretch RF frequencies of 3 to 5.5 GHz at stretch factors 2 to 15. Our calculations showed that the power efficiency of the PTS system is periodically fluctuating across the stretch factors and frequencies. Also, we observed that there is a variation in the power of the frequency components of stretched signal compared to expected. This is because our results showed that the RMSE varies per stretch in the frequency domain., which indicates that the power distribution in the frequency spectrum varies. Aside from that, we performed a loss calculation for an actual implementation of a PTS system in different scenarios. We observed that the power of the carrier and reflectance of the connectors greatly affects the output power. For a stretch factor of 5 at short fiber lengths, our highest calculated output power is -25.34 dBm at high carrier power, using single-mode fiber optic cable. On he other hand, for the same stretch at long fiber lengths, our highest calculated output power is -16.69 dBm at high carrier power, using single-mode fiber optic cable.
Thesis (Master of Science in Electrical Engineering)--University of the Philippines Diliman
Keywords: Photonics